If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10n + 15 = 9n + 6n Reorder the terms: 15 + 10n = 9n + 6n Combine like terms: 9n + 6n = 15n 15 + 10n = 15n Solving 15 + 10n = 15n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-15n' to each side of the equation. 15 + 10n + -15n = 15n + -15n Combine like terms: 10n + -15n = -5n 15 + -5n = 15n + -15n Combine like terms: 15n + -15n = 0 15 + -5n = 0 Add '-15' to each side of the equation. 15 + -15 + -5n = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -5n = 0 + -15 -5n = 0 + -15 Combine like terms: 0 + -15 = -15 -5n = -15 Divide each side by '-5'. n = 3 Simplifying n = 3
| (3x^3/z)^3 | | 6x+21=7(x+3) | | 1-4k=-5k-1 | | -6-a=1+6a | | 5x-3=10x | | -5k+10k+16=1+2k | | -12x-14=-74 | | 5(8+7c)=390 | | 3x+15x+7=162 | | 7a-2=10+7a+4a | | 3/5x-2/3 | | 3/5x-2/5 | | -2+5v=9v+10 | | 12-9b=6-8b | | 2u+8u-5u= | | An=1/27*3^n-1 | | 1-8x=-7-6x | | 3/5x-2/5=3/10 | | -(3x-3)=-6-2x | | 17-9n=1-7n | | 4/3=v/8 | | 2x-5x=-5-2x | | 3r-6=2r-2r | | 0=3b+21 | | 1+3p=-4p+15 | | -18+7m=m-6-6 | | Y/3-3=11 | | 6n-14=4n+16 | | k-6=m+18 | | 3x=y+16 | | 3(-2x+1)=7(-3x-6) | | 7(5-2a)=5(-3a+1) |